Can single-step dilatation technique in pediatric percutaneous nephrolithotomy be an effective alternative to stepwise dilatation? - Uçar, Murat; Kısa, Erdem; Çelik, Fatih; Yücel, Cem; Süelözgen, Tufan; İlbey, Yusuf Özlem and Kılıç, Nizamettin (Journal of Surgery and Medicine, 2019)
Aim: The most important stage of percutaneous nephrolithotomy (PNL), which is an effective and reliable method in the treatment of large and complex kidney stones, is to create a suitable and effective tract after the accessory is provided. For this purpose, different techniques such as Amplatz, baloon and Alken dilators have been described. We aimed to compare the efficacy and safety of single-step Amplatz dilatation technique with stepwise Amplatz dilatation technique in pediatric PNL patients. Methods: This is a retrospective cohort study. We evaluated the data from 75 PNL operations performed on 72 pediatric patients in our center within the last decade. The data from single-step dilation technique patient group (group 1, n: 41) and the stepwise dilatation technique patient group (group 2, n: 34) was compared in terms of durations of fluoroscopy and surgery, stone-free and complication rates, pre and postoperative hematocrit levels and blood transfusions rates. Results: There was no significant difference between the groups in terms of demographic data, mean stone burden, duration of surgery, decrease in hematocrit, blood transfusion rates, stone-free rate and complication rates. The median fluoroscopy durations of group 1 and group 2 were 120 and 220 seconds, respectively. Duration of surgery and fluoroscopy were significantly shorter in the single-step dilatation group Conclusion: PNL is a safe and effective procedure for pediatric stone diseases. Performing this procedure with a single-step dilatation technique ensures that children are less exposed to radiation.